Pengaruh Live Streaming Shopping Terhadap Impulsive Buying Behavior Pada Generasi Z: Studi Kasus Pengguna Tiktok Shop di Kota Pangkal Pinang - Hengki Hengki; Desvira Afsari (SENTRI: Jurnal Riset Ilmiah, 2026)
Live shopping through social media and e-commerce platforms has become a major driver of digital marketing transformation, fundamentally changing the way consumers shop and businesses promote their products. One of the key advantages of live streaming shopping is its interactive nature, which bridges the gap between digital and physical shopping experiences by allowing consumers to view products in real time, communicate directly with sellers, and access exclusive promotional offers and discounts. These interactive features are believed to stimulate consumers' spontaneous purchasing decisions. This study aims to examine the influence of live streaming shopping on consumers' impulse buying behavior. A quantitative approach was employed by distributing questionnaires to respondents who had previously used live streaming shopping features. The collected data were analyzed using SPSS, including validity and reliability tests, simple linear regression, hypothesis testing, and coefficient of determination analysis to ensure data quality and evaluate the proposed relationship. The findings indicate that live streaming shopping has a positive and statistically significant effect on impulse buying behavior. High-quality interactive communication and frequent real-time engagement between sellers and consumers during live streaming sessions were identified as the primary factors encouraging spontaneous purchasing decisions. Furthermore, the coefficient of determination demonstrates that live streaming shopping accounts for a substantial proportion of the variation in consumers' impulse buying behavior. This study contributes to the growing body of knowledge on consumer behavior and digital marketing by providing empirical evidence that live streaming shopping serves as an effective marketing stimulus capable of triggering consumers' impulsive purchasing responses.